The Effect of Sponsorship Events and Prices on Interest in Buying Sampoerna A-Mild Cigarettes in Banjarmasin City - NurAzizah; HasanurArifin; SetioUtomo; Humaidi (Magister Administrasi Bisnis ULM, 2024)
that have limitations in promotion. This study aims to determine the effect of sponsorship events and prices on buying interest. Respondents in this study were buyers of Sampoerna A-Mild cigarettes in Banjarmasin City who were taken using a simple random sampling technique. So that 50 respondents who bought Sampoerna A-Mild cigarettes were obtained as research samples. The data used were taken from a questionnaire made by the author himself. Data analysis used descriptive analysis and multiple linear regression analysis. The results showed that partially the Event Sponsorship variable had a significant effect on Buying Interest in Banjarmasin with a large influence of38.7%, the Price variable had a partially significant effect on Buying Interest with a large influence of 38.9%, simultaneously the Event Sponsorship variable and Price has a significant effect on Buying Interest with a large effect of44.9%.